(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
The electromagnetic field’s morphing in interaction with blood flow may be used to propose a novel bioimpedance technique aimed at the non-invasive detection and mapping of large cerebral vascular networks, such as the dural venous sinuses, which collect the venous deoxygenated blood from the brain region and returns it to the heart through the internal jugular vein and the superior vena cava. In this impedance method, the position of the electrodes on the skull leads the incident flux (the electric current density) to outline the vascular flow and spot the venous sinuses noninvasively. It is crucial for some neurosurgical interventions that the venous sinuses are not accidentally damaged during the procedure since hemorrhage at this level is often fatal.